Thermal Behavior and Microscopic Characteristics of Water-soaked Coal Spontaneous Combustion. Issue 3 (17th February 2022) - Huang, Zhian; Li, Jinyang; Gao, Yukun; Shao, Zhenlu; Zhang, Yinghua
ABSTRACT: The current reaction kinetics of coal–oxygen compound in water-soaked coal has not been accurately explained. Therefore, thermal behavior and microscopic characteristics during spontaneous combustion of water-soaked coal samples were analyzed. Five kinds of coal samples were selected with moisture contents of 5%, 10%, 15%, and 20% of the raw coal. Fourier transform infrared (FTIR), thermogravimetric (TG), and diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) were adopted. The results showed that the hydroxyl (–OH) group is greatly affected by the moisture content of coal samples. The area of hydroxyl absorption peaks in coal samples with 5% and 10% moisture content increased by 1.76% and 1.12%, respectively. The critical temperature T1 decreased the most at 10% moisture content compared with the raw coal, which was about 6.5 °C. This indicated that the heat storage process was accelerated and the activity of the coal samples was increased. According to the thermodynamic analysis, the activation energy of the five kinds of water-soaked coal samples are 148.078 kJ/mol, 147.674 kJ/mol, 146.197 kJ/mol, 145.019 kJ/mol, and 145.934 kJ/mol, respectively. This proves that the activation energy of coal samples is generally reduced after immersion in water, and coal samples with 15% moisture content are most susceptible to spontaneous combustion. As the temperature was raised, aliphatic hydrocarbons (–CH3, – CH–) and C = O increased rapidly. The above results indicate that water immersion accelerates the spontaneous combustion and oxidation of coal to a certain extent.